Perancangan Sistem Informasi Peminjaman Berkas Rekam Medis di RSUD Al-Ihsan: . - Aura Aurellia; Deasy Laela Nursari; Yuda Syahidin; Yuyun Yunengsih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
This study aimed to evaluate current systems and processes as well as design and build a medical record lending information system using Visual Studio 2012 at Al-Ihsan Regional Hospital in Bandung. The research method used is qualitative research with data collection through observation, interviews, internet browsing and information system design within a system development framework built using the waterfall method using the Microsoft Visual Studio 2012 tool. In this study, several problems were found in the medical record borrowing process, among others, inefficiencies in the document borrowing system, the use of using Excel-based manuals, as well as obstacles in obtaining documents. It is suggested that a system designed to record loans be used to speed up the process and manage duplicate data more effectively.